Strengthening National Identity Through Civic Education in Grade V Elementary School Students - Armawati Armawati; Susilasari Susilasari; Marwan Marwan; Zulhidah Zulhidah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
National identity is a fundamental pillar that needs to be instilled in the younger generation from an early age. This study aimed to describe efforts to strengthen national identity through Civics Education (PKn) for fifth-grade elementary school students. Using a descriptive qualitative approach, this research involved 2 PKn teachers and 30 Grade V students at one elementary school in Pekanbaru, Riau, selected through purposive sampling based on criteria including active involvement in PKn learning and willingness to participate in the study. Data were collected through classroom observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model comprising data reduction, data display, and conclusion drawing, with source and method triangulation to ensure validity. The findings reveal three key strategies for strengthening national identity: (1) integration of national values (Pancasila, the 1945 Constitution, Bhinneka Tunggal Ika, and NKRI) into PKn learning content through interactive discussions, storytelling, and contextual case studies; (2) nationally-oriented school habituation through flag ceremonies, national anthem singing, and national literacy programs; and (3) student activity-based projects such as patriotic posters, hero narratives, and deliberation simulations. These strategies work synergistically to internalize national values across cognitive, affective, and psychomotor domains. In conclusion, PKn is effective as a vehicle for building national character in elementary school students, equipping them with the values and civic awareness needed to become responsible, patriotic, and globally competent citizens.